Iacopo, i sogni e il monte calamita. Le fonti filosofiche del trattato sui sogni dello Specchio di vera penitenza - Tromboni, Lorenza (Bulletin de Philosophie Médiévale, 2017)
Abstract The article analyses the chapter on dreams of the Specchio di vera penitenza by Iacopo Passavanti, a Dominican friar who lived in 14th century Florence, focusing on the philosophical sources employed by the preacher. This section of the Specchio is in fact peculiar, since Iacopo discusses here the value of dreams for human knowledge by means of Aristotelian concepts and doctrines, but it does not mention them explicitly. Moreover, while discussing on dreams, Iacopo lingers on the myth of the magnetic mountain following the pseudo-Aristotelian De lapidibus and the treatise On Minerals by Albert the Great. The article studies also Passavanti’s other sources concerning this passage, such as the De lapidibus by Marbodus of Rennes and the Speculum historiale by Vincent of Beauvais.